Damage Mapping as a Diagnostic Tool for Pathological Manifestations in Historical Buildings: A Literature Review - Vasconcelos, Felipe Duan Moura; Gonzaga, Camila Marques do Rêgo; Rabbani, Emilia Rahnemay Kohlman; Monteiro, Eliana Cristina Barreto; Souza, Juliana Santa Cruz (National Journal of City Management, 2025)
Objective – To analyze the application of damage mapping techniques for the identification of pathological manifestations in historical buildings, considering their relevance for the preservation of cultural heritage. Methodology – A Systematic Literature Review was conducted based on the PRISMA protocol, using specific criteria for the selection, evaluation, and synthesis of articles. The selected studies were analyzed through quantitative aspects (year of publication, researchers’ origin, and frequency of keywords) and qualitative aspects (types of analyses, structures studied, and methodologies employed to investigate pathological manifestations), chosen due to their relevance to the research context. Originality/Relevance – The study stands out for gathering and systematizing the main approaches to the use of damage maps in historical constructions, contributing to the understanding of the state of the art and consolidating this technique as a reference tool in cultural heritage conservation. Results – The findings revealed a continuous evolution in research employing damage maps, showing advances in complementary methodologies. It was also identified that this technique has increasingly been integrated with other analytical tools, enhancing its accuracy and reliability. Theoretical/Methodological Contributions – The study provides a structured synthesis of the application of damage maps, presenting relevant parameters for future research and highlighting gaps to be explored. Furthermore, it suggests methodological ways to improve practice by integrating the technique with more robust analytical methods. Social and Environmental Contributions – By strengthening the preservation of historical heritage, the advances discussed in this work contribute to the appreciation of collective memory and cultural identity. From an environmental perspective, the improvement of conservation practices reduces the need for invasive interventions and material waste, favoring more sustainable restoration strategies.